Heterose, depressão endogâmica e ação gênica em cruzamento de algodão herbáceo, Gossypium hirsutum L. r. latifolium Hutch., e algodão moco, Gossypium hirsutum L. r. marie galante Hutch - Costa Neto, Francisco Vieira (1985)
Studies about heterosis, inbreeding depression, and gene action were carried out in crosses between annual cotton, Gossypium hirsutum L. r. latifolium Hutch., and perennial cotton, Gossypium hirsutum L. r. marie galante Hutch. [...]